2015
DOI: 10.1093/asj/sjv094
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Seeking Minimally Invasive Cosmetic Procedures in an Academic Outpatient Setting

Abstract: 4 Therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 28 publications
5
64
1
1
Order By: Relevance
“…Ability to afford treatment commonly influenced timing of treatment. This finding is consistent with that of Sobanko et al 11 that financial limitations were the greatest hindrance to pursuing treatment. Payment plans, package discounts for multiple treatments, or more widely spaced intervals between sessions may improve access to treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Ability to afford treatment commonly influenced timing of treatment. This finding is consistent with that of Sobanko et al 11 that financial limitations were the greatest hindrance to pursuing treatment. Payment plans, package discounts for multiple treatments, or more widely spaced intervals between sessions may improve access to treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Also, approximately a quarter of patients reported the use of psychiatric medication (an antidepressant, antipsychotic, or anxiolytic) at the time of treatment. 32 Another study showed a significant positive correlation between interest in cosmetic procedures and burn-out syndrome. The authors claimed that this correlation between burn-out syndrome and interest in cosmetic surgery could reveal a way of coping with the stress.…”
Section: Discussionmentioning
confidence: 97%
“…In another prospective, single‐institution cohort study of 72 patients who were seeking MICPs, it was noted that almost one‐third of patients experienced a major life event within the preceding year, defined as either a birth or death in the family, a new job or loss of a job, a marriage, or a divorce. Also, approximately a quarter of patients reported the use of psychiatric medication (an antidepressant, antipsychotic, or anxiolytic) at the time of treatment . Another study showed a significant positive correlation between interest in cosmetic procedures and burn‐out syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, aesthetic surgery to the eye region may be one of the most effective interventions in enhancing the overall appearance of an individual [1] . A recent prospective study on 72 female patients with an average age of 48 years, showed that 74.6% of these patients felt that their first sign of ageing occurred in the eyes, 26.7% in the neck and only 12.6% in the cheeks [2] . Among this female group, 78.8% of patients expressed interest in improving the appearance of their eyes, 28.8% the cheeks and lips only 15% [2] .…”
Section: Introductionmentioning
confidence: 99%